Urban functions in rural development - Sinha, B. L.; Singh , Jagdish (ed.) (Gorakhpur, 1990)
No branch of human geographical studies has engaged the attention of as many geographers all over the world as the studies related to "Central Places' especially after the publica tion of Walter Christaller's now classic study. This is because it has given a theoretical foundation to the subject and ope ned a new vista for elucidation, extension and verification of the central place theory with respect to different cultural realms and economic regions. Apart from its value as an academic exercise it has, recently, opened a new horizon in the field of applied geography. Central place system in any region is regarded as the structural base for the forces and processes of economic development. Economic development is essentially a matter of the origin and spread of innovations and a central place system regulates the process of innovation-diffusion. As such, a region having an articulated system of central pla ces is better poised to absorb, spread and hasten the trickling down of innovations that usually spring from the old establi shed metropolises. In India, too, central place systems have been studied from both the viewpoints i. e.. theoretical and applied, at different regional scales. However, no study of the central place system of Mithila plain, a region forming a dis tinct cultural entity within the great plain of India has been made so for. This region, whose cultural roots extend into the antiquity and which has the credit of giving rise to democra tic system of government much before it was even dremt of in Europe and, thus, was a centre of great innovation now constitutes one of the poorest peripheral regions of the country. In order to revitalise the economy of the region by adopting UFRD strategy a study of its central place system would be inevitable.
Keywords: Rural development